PENGARUH PERBANDINGAN TEPUNG TALAS, TEPUNG JAGUNG, DENGAN TEPUNG PISANG DAN PERSENTASE KUNING TELUR TERHADAP MUTU FLAKES TALAS (The Effect of Taro Flour Ratio, Corn Flour, with Banana Flour and Yolk Percentage an Taro Flakes Quality) - Triana Aulia; Ismed Suhaidi; Herla Rusmarilin (Universitas Sumatera Utara, 2017)
ABSTRACT The purpose of this research was to found the effect of taro flour ratio, corn flour, with banana flour and yolk percentage on the quality of taro flakes. The study was performed in May – July 2016 at the Laboratory of Food Technology, Faculty of Agriculture, University of Nort Sumatra, Medan, was using factorial completely randomized block design with two factors i.e ratio of taro flour, corn flour, with banana flour (P) (80:10:10; 70:20:10; 60:30:10; and 50:40:10) and yolk percentage (T) (2%; 4%; 6%; and 8%). The parameters that analyzed were water content, ash content, fat content, protein content, carbohydrate content, crude fiber content, water absorption, resilience crisp in the milk, texture, organoleptic test of color, flavor, taste, and acceptance of panelist. The research showed that the ratio of taro flour, corn flour, with banana flour had a highly significant effect on water content, protein content, carbohydrate content, texture, organoleptic test of color and acceptance of panelist while the yolk percentage had a highly significant effect on water content, fat content, protein content, carbohydrate content, texture, organoleptic test of color and acceptance of panelist and had no significant effect on ash content, crude fiber content, water absorption, resilience crisp in the milk, organoleptics test of taste and flavor. The interaction between the two factors had significantly effect on water content, texture, organoleptic test of color, and acceptance of panelist.the best taro flakes way the P4T3 treatment was the ratio of taro flour, corn flour, with banana flour (50:40:10) and yolk percentage was 6%. Keywords: banana flour, corn flour. taro flake,taro flour, yolk ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh perbandingan tepung talas, tepung jagung, dengan tepung pisang dan persentase kuning telur terhadap mutu flakes talas. Penelitian ini dilakukan pada bulan Mei - Juli 2016 di Laboratorium Teknologi Pangan, Fakultas Pertanian, Universitas Sumatera Utara, Medan, menggunakan Rancangan Acak Lengkap yang terdiri dari dua faktor yaitu perbandingan tepung talas, tepung jagung, dengan tepung pisang (P) (80: 10:10; 70:20:10; 60:30:10; dan 50:40:10) dan persentase kuning telur (T) dengan empat taraf yaitu (2%; 4%; 6%; dan 8%). Parameter yang dianalisis adalah kadar air, kadar abu, kadar lemak, kadar protein, kadar karbohidrat, kadar serat kasar, daya serap air, ketahanan renyah dalam susu, tekstur, dan organoleptik (warna, aroma, rasa, dan penerimaan panelis). Hasil penelitian menunjukkan bahwa perbandingan tepung talas, tepung jagung, dengan tepung pisang memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar protein, kadar karbohidrat, kadar serat kasar, daya serap air, kerenyahan dalam susu, uji tekstur, organoleptik warna, aroma, rasa, dan penerimaan panelis sedangkan persentase kuning telur memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar lemak, kadar protein, kadar karbohidrat, tekstur, organoleptik warna, dan penerimaan panelis serta memberikan pengaruh berbeda tidak nyata terhadap kadar abu, kadar serat kasar, daya serap air, kerenyahan dalam susu, organoleptik aroma dan rasa. Interaksi antara kedua faktor memberikan pengaruh berbeda sangat nyata terhadap kadar air, tekstur, organoleptik warna, dan penerimaan panelis. Formulasi flakes talas terbaik terdapat pada perlakuan P4T3 yaitu perbandingan tepung talas, tepung jagung, dengan tepung pisang (50:40:10) dan persentase kuning telur 6%. Kata Kunci : flakes talas, kuning telur, tepung jagung, tepung pisang, tepung talas,